Impulsivity and neuroticism share distinct functional connectivity signatures with alcohol-use risk in youth - Cheng, Annie; Lichenstein, Sarah; Chaarani, Bader; Liang, Qinghao; Babaeianjelodar, Marzieh; Riley, Steven J.; Luo, Wenjing; Horien, Corey; Greene, Abigail S.; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; et al. (Molecular psychiatry, 2025)
Increases in impulsivity and negative affect (e.g., neuroticism) are common during adolescence and are both associated with risk for alcohol-use initiation and other risk behaviors. Whole-brain functional connectivity approaches—when coupled with appropriate cross-validation—enable identification of complex neural networks subserving individual differences in dimensional traits (hereafter referred to as ‘neural signatures’). Here, we analyzed functional connectivity data acquired at age 19 from individuals enrolled in a multisite European study of adolescent development (N ~ 1100) using connectome-based predictive modeling. Network anatomies of these dimensional phenotypes were compared with one another and with a previously identified alcohol-use risk network to identify shared and unique neural mechanisms. Models accurately predicted both impulsivity and neuroticism (r’s ~ 0.17-0.19, p’s < 0.05), and successfully generalized to an external sample. The impulsivity network was predominantly characterized by motor/sensory-related connections. By contrast, the neural signature of neuroticism was relatively more distributed across multiple canonical networks, including motor/sensory, default mode, subcortical, frontoparietal and cerebellar networks. Very few connections were common to both impulsivity and neuroticism networks. Moreover, while ~10-20% of the connections from each trait overlapped with the alcohol-use risk network, these connections were distinct between the two traits. This study for the first time identifies functional connectivity signatures of two common risk factors for alcohol-use in youth—impulsivity and neuroticism. Consistent with current equifinality-based conceptions of development, few connections predicted both impulsivity and neuroticism, indicating that the neural signatures of these two traits are relatively distinct despite both being implicated in alcohol-use risk and a wide array of behaviors.
Gesehen am 14.10.2025